Perineuronal nets in brain physiology and disease. (May 2019) - Testa, Damien; Prochiantz, Alain; Di Nardo, Ariel A.
Abstract: Perineuronal nets (PNNs) in the brain are condensed glycosaminoglycan-rich extracellular matrix structures with heterogeneous composition yet specific organization. They typically assemble around a subset of fast-spiking interneurons that are implicated in learning and memory. Owing to their unique structural organization, PNNs have neuroprotective capacities but also participate in signal transduction and in controlling neuronal activity and plasticity. In this review, we define PNN structure in detail and describe its various biochemical and physiological functions. We further discuss the role of PNNs in brain disorders such as schizophrenia, bipolar disorder, Alzheimer disease and addictions. Lastly, we describe therapeutic approaches that target PNNs to alter brain physiology and counter brain dysfunction.